2020
DOI: 10.1088/1742-6596/1644/1/012060
|View full text |Cite
|
Sign up to set email alerts
|

Gas sensing behavior of ZnO thick film sensor towards H2S, NH3, LPG and CO2.

Abstract: - ZnO is synthesized by microwave assisted technique. The XRD, TEM, SAED and SEM characterization of sample is carried out for studying crystal structure, particle size, crystalline nature and surface morphology of ZnO samples. The thick films of ZnO sample were fabricated by screen printing technique and its I-V characteristics and electrical conductivity were studied. The gas sensing response of ZnO thick film sensor towards 450 ppm of H2S, LPG, NH3 and CO2 gas was investigated. The thick film showed respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Response of the prepared thin films was increasing linearly for increasing gas concentration. [ 18,19 ] The enhanced response and recovery time of the Mn 0.5 Zn 0.5 Fe 2 O 4 thin film is observed from Figure 5.…”
Section: Resultsmentioning
confidence: 95%
“…Response of the prepared thin films was increasing linearly for increasing gas concentration. [ 18,19 ] The enhanced response and recovery time of the Mn 0.5 Zn 0.5 Fe 2 O 4 thin film is observed from Figure 5.…”
Section: Resultsmentioning
confidence: 95%
“…[ 86 ] It is well known that the sensor surface resistance increases with the adsorption of oxidizing gases like O 2 or CO 2 and vice versa for reducing gasses like CO or C 3 H 8 . [ 87 ] This resistance change happens due to the transfer of charge carried from the semiconductor to the adsorbed gas molecule, specifically electrons in the case of an n‐type semiconductor like ZnO. Therefore, the sensing response of a semiconductor can be increased by raising the number of electrons transferred due to the presence of a test gas.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO nanoparticles show promising properties for various device applications like transparent electrode in solar cell, chemical sensor [5][6][7], humidity sensor [8], UV photo sensor and high power FETs. The literature study revealed a variety of synthesis methods for producing ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%